0226 Circadian influence on food intake among adolescents with overweight and healthy weight. (25th May 2022) - Barker, David; Carskadon, Mary; Gredvig-Ardito, Caroline; Hart, Chantelle; Raynor, Hollie; Scheer, Frank
Abstract: Introduction: Meal timing has been linked to obesity in adults and children; however, evidence for an endogenous influence of the circadian system on food intake is unknown. We measured food intake during forced desynchrony (FD) in adolescents with healthy weight (HW) or overweight (OW), hypothesizing that circadian timing would affect food intake independent of the environmental cycle and that the food intake rhythm would be delayed in adolescents with OW compared to HW. Methods: Participants were 51 (29m) adolescents (12-15yr); 24 were HW and 27 OW determined by CDC norms. Participants completed seven, 28h-FD cycles; 6 meals occurred at fixed times each cycle with foods selected 1h before meals and weighed before and after. Each meal's energy intake was computed relative to total energy consumed in that FD cycle. Endogenous circadian period was determined using salivary dim-light melatonin onset (DLMO) phases (DLMO=0°). Time awake effect was assessed using mixed effect models and circadian phase with multilevel cosinor that included time awake as a categorical covariate. Results: Circadian period was not significantly different between OW and HW (mean, StDev; HW =24.19h, 0.22; OW=24.22h, 0.14). Overall, participants consumed more calories on the cycles' first meals (22.0% [21.3;22.6]) compared to the last meal (12.4% [11.8;13.0]). Adolescents with OW vs. HW consumed a higher proportion of calories later in the wake episode (F(5, 2081)=2.63, p=.02). As hypothesized, circadian phase influenced caloric intake with an amplitude of 2.66% [2.19;3.14] percent daily calories and an acrophase of 301°[291;310], equivalent to 17:52 in this population. The circadian influence differed by weight category (likelihood ratio test of both amplitude and acrophase; χ2(2)=10.7, p<.01), with those with OW showing a lower amplitude (OW = 2.11%[1.40;2.82], HW=3.53%[2.94;4.12] and later acrophase (OW=301° [287;314], HW=290° [278;302]). Conclusion: Results show for the first time an independent influence of the endogenous circadian timing system on caloric intake of humans that differed as a function of body weight: caloric intake for adolescents with OW had a circadian rhythm with blunted amplitude and delayed peak phase. These observations show circadian control of food intake that may be stronger in HW than OW adolescents. Support (If Any): P20GM139743; R01DK101046; R01HL153969